Coordinating adoption decisions under externalities and incomplete information - Aoyagi, Masaki (Games and economic behavior, 2013)
A monopolist sells a good whose value depends on the number of buyers who adopt it as well as on their private types. The seller coordinates the buyersʼ adoption decisions based on their reported types, and charges them the price based on the number of adoptions. We study ex post implementable sales schemes that are collusion-proof, and show that under the revenue maximizing scheme, more buyer types are willing to adopt when there are more adoptions, and the number of adoptions is maximized subject to the participation constraints. ► The value of a good to a buyer depends on his private type and the number of adopting buyers. ► A monopolist seller coordinates adoption decisions and engages in adoption-contingent pricing. ► A revenue maximizing coalitionally implementable coordinating scheme is studied. ► An optimal scheme is shown to have a simple monotonicity property.